Iron(III) Catalyzed Coupling of Aryl Halides: Synthesis of Terphenyl and Biphenyl Derivatives - Rahman, M. J.; Debnath, D. (Journal of Scientific Research, 2012)
Iron(III) mediated coupling of arylmagnesium halides with other aryl halides produced both homo- and cross-coupled products. The reaction of phenylmagnesium bromide with 1,4-dibromobenzene as well as with 4-chlorobromobenzene in presence of FeCl3 catalyst produced both cross-coupled p-terphenyl and homo-coupled biphenyl. Under the same condition only homo-coupled 4,4¢-dipropoxybiphenyl was obtained from 4-propoxyphenylmagnesium bromide. The coupling of 4-bromophenylmagnesium bromide with bromobenzene produced both homo- and cross-coupled biaryls. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.12207 J. Sci. Res. 5 (1), 127-134 (2013)